2015
DOI: 10.1073/pnas.1505953112
|View full text |Cite
|
Sign up to set email alerts
|

KTKEGV repeat motifs are key mediators of normal α-synuclein tetramerization: Their mutation causes excess monomers and neurotoxicity

Abstract: α-Synuclein (αS) is a highly abundant neuronal protein that aggregates into β-sheet-rich inclusions in Parkinson's disease (PD). αS was long thought to occur as a natively unfolded monomer, but recent work suggests it also occurs normally in α-helix-rich tetramers and related multimers. To elucidate the fundamental relationship between αS multimers and monomers in living neurons, we performed systematic mutagenesis to abolish self-interactions and learn which structural determinants underlie native multimeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
184
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(205 citation statements)
references
References 35 publications
15
184
1
Order By: Relevance
“…In addition, lysine-to-glutamate mutations in those repeats alter aSyn binding to membrane phospholipids [45]. A similar mutant, seven-times KLKEGV, has recently been described by us to abolish native aSyn tetramers/multimers in neurons [46 ]. Other repeat motif mutants, such as KTKEIV and KTKKGV, abolished native multimerization as well, and this was invariably accompanied by an enrichment of the protein in PBSinsoluble fractions that required Triton-X 100 for solubilization, presumably representing more membrane association.…”
Section: Cytoplasmic Vs Membrane-bound Asynimplications For Functionmentioning
confidence: 74%
“…In addition, lysine-to-glutamate mutations in those repeats alter aSyn binding to membrane phospholipids [45]. A similar mutant, seven-times KLKEGV, has recently been described by us to abolish native aSyn tetramers/multimers in neurons [46 ]. Other repeat motif mutants, such as KTKEIV and KTKKGV, abolished native multimerization as well, and this was invariably accompanied by an enrichment of the protein in PBSinsoluble fractions that required Triton-X 100 for solubilization, presumably representing more membrane association.…”
Section: Cytoplasmic Vs Membrane-bound Asynimplications For Functionmentioning
confidence: 74%
“…Trexler and Rhoades [31] have demonstrated that N-terminal acetylation is critical for forming α-helical oligomers of α-syn. Further evidence for the tetrameric conformation has been obtained by Bartels et al [32], Pochapsky [33] and Dettmer et al [34]. As noted by Trexler and Rhoades [31], acetylation removes the N-terminal charge, making this region more hydrophobic.…”
Section: Distribution Of Mitochondrial-targeting Sequences and C-termmentioning
confidence: 78%
“…All α-syn isoforms also contain multiple highly conserved phospholipid-binding motifs (KTKE(Q) G(Q)V), thought to mediate binding to phospholipid membranes (e.g. [34]), which in the tetramer would involve up to 16 phospholipid binding (KTKE(Q)G(Q)V) motifs. Cholesterol-containing pore-lining regions are known to form Ca 2+ ion channels [18,26] which together with the EF-hand in the C-terminal region of the molecule would regulate Ca 2+ movement across the mitochondrial membrane.…”
Section: Resultsmentioning
confidence: 99%
“…These occur in the N-terminal third of the protein and may induce structural changes that decrease the intramolecular interaction between the N and C termini (3) and/or decrease the intermolecular propensity to form α-helical tetramers and related multimers (4). Interfering with the latter process can lead to an excess of unfolded monomers prone to abnormal oligomerization (5). In rare families that inherit αSyn gene multiplication, a causal link between the lifelong increase in monomer levels, neurotoxicity, and PD is likely (6).…”
mentioning
confidence: 99%